Acute flaccid paralysis surveillance in bosnia and herzegovina: Recent isolation of two sabin like type 2 poliovirus. Issue 9 (23rd May 2017) - Fontana, Stefano; Buttinelli, Gabriele; Fiore, Stefano; Mulaomerovic, Mirsada; Aćimović, Jela; Amato, Concetta; Delogu, Roberto; Rezza, Giovanni; Stefanelli, Paola
Abstract : The WHO Regional Commission for the Certification of Poliomyelitis Eradication has recently indicated Bosnia and Herzegovina (B&H) as a high risk country for transmission, following importation, of wild poliovirus (WPV) or circulating vaccine‐derived poliovirus (cVDPV). We analyzed data on Acute Flaccid Paralysis (AFP) surveillance between 2007 to 2016, and the trend of polio immunization coverage in B&H. The majority of AFP cases was recorded in 2016 suggesting an enhancement of the AFP surveillance activities. However, the decline in the immunization coverage, around 74%, and the isolation of two Sabin‐like poliovirus type 2 strains, one of them close to a VDPV, require a particular attention in the area. Although B&H has successfully maintained its polio‐free status since 2002 several challenges need to be addressed.